Topical Immunosuppressant Agent Cyclosporine (CsA) as Therapy for Ocular Alkali Chemical Injury: Is It Really Beneficial? Poster Presentation - Case Report - General practitioner - Rijena Karina Abigael F .K. Bangun; Balgis Desy Sulistyowati (Majalah Oftalmologi Indonesia, 2023)
Introduction : Alkali chemicals can cause more severe ocular injury than acidic chemicals, because the alkali can rapidly penetrate the cornea into the anterior chamber of the eye and damage the iris, ciliary body, lens and trabecular meshwork, which can cause significant visual impairment. A topical immunosuppressant Cyclosporine (which also known as Cyclosporin A or CsA) was used in the treatments. Case Illustration : A 3-year-old male patient presented painful eyes 3 days after an accidental ocular injury with Calcium Hydroxide. The ophthalmic examination revealed based on Roper-Hall grading, the injuries indicated grade III-IV ODS. The patient's BCVA OD 2/60, and OS 20/200. The patient was hospitalized and underwent intensive conservative pharmacological therapy, including topical CsA. Corneal healing was examined by serial corneal Optical coherence tomography (OCT) and showed improvement of the corneal haze throughout the follow-ups. From the last follow-up, the BCVA OD 20/70, OS 20/40. Discussion : Topical CsA reduces the number of CD3-positive cells (T lymphocytes) and the production of pro- inflammatory cytokines, which was associated with the decreased expression of matrix metalloproteinase-9, inducible nitric oxide synthase, VEGF and active caspase-3. Corneal neovascularization is a clinical condition caused by alkali burn that, when left untreated, leads to significant visual impairment. VEGF-A is one of the most important mediators of angiogenesis, leading to neovascularization. Hence, topical CsA 0.1% eye drops may play a role in the treatment of alkali corneal injury. Conclusion : This case report showed that topical CsA gave a significant corneal wound healing, combined with the mainstay of alkali chemical injury.